2016
DOI: 10.1063/1.4955077
|View full text |Cite
|
Sign up to set email alerts
|

Electric field dynamics in nitride structures containing quaternary alloy (Al, In, Ga)N

Abstract: Molecular beam epitaxy growth and basic physical properties of quaternary AlInGaN layers, sufficiently thick for construction of electron blocking layers (EBL), embedded in ternary InGaN layers are presented. Transmission electron microscopy (TEM) measurement revealed good crystallographic structure and compositional uniformity of the quaternary layers contained in other nitride layers, which are typical for construction of nitride based devices. The AlInGaN layer was epitaxially compatible to InGaN matrix, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…However, most of the TRPL analyses presented here were performed at low temperature of about 6 K. The low-temperature signal from GaN was at 3.47 eV, as expected. Its lifetime was about 0.1 ns, which is significantly faster than in GaN homoepitaxial material [36,37] or pure GaN nanowires [38]. It was observed that the signal from the CQWs was very strong up to 300 K.…”
Section: B Time-resolved Plmentioning
confidence: 97%
“…However, most of the TRPL analyses presented here were performed at low temperature of about 6 K. The low-temperature signal from GaN was at 3.47 eV, as expected. Its lifetime was about 0.1 ns, which is significantly faster than in GaN homoepitaxial material [36,37] or pure GaN nanowires [38]. It was observed that the signal from the CQWs was very strong up to 300 K.…”
Section: B Time-resolved Plmentioning
confidence: 97%